STEREOTIP ANTARA ETNISTIONGHOA DAN ETNIS JAWA PADA SISWA SMA SANTA THERESIA (Studi Analisis Pendidikan Islam Multikultural) - Ariasih, Luh Putu (JURNAL AT-TURAS, 2016)
Race and ethnicity conflict between Chinese and Javanese has generated strong stereotypes between the two. But years after the riot resolved, thing has changed. The government has acknowledged the Chinese community as part of the nation. This study would like to obtain the stereotypical views between Chinese and Javanese students in SMA Santa Theresia. Researchers used the descriptive-qualitative method with indepth interview, observation, and documentation added and proceed by data triangulation. Respondents has chosen by purposive sampling with consideration of ethnicity difference and interaction qualities. Dataanalysed by using Miles and Huberman’s analysis model which consist of data reduction and display, and conclusion drawing. The result of the study shows that stereotype arose is individual ones and they do not influence the interaction between Chinese and Javanese students. This caused by the difference in interaction quantity between students and the school management which do not classify students based on their ethnicities and places of origin.